A Positive Feedback Loop of lncRNA DSCR8/miR-98-5p/STAT3/HIF-1α Plays a Role in the Progression of Ovarian Cancer - Dong, Lina; Cao, Xuejiao; Luo, Yi; Zhang, Guoqing; Zhang, Dandan (Frontiers in Oncology, 2020)
Background Accumulating studies have revealed that long noncoding RNA (lncRNA) and microRNA (miRNA) contribute to ovarian cancer (OC). DSCR8 has been found to mediate hepatocellular carcinoma development, while its role in OC remains to be explored. Methods In this study, lncRNA DSCR8 and miR-98-5p expressions in OC tissues and adjacent non-cancer tissues were determined by reverse transcriptase polymerase chain reaction (RT-PCR). Besides, gain- or loss- assays of DSCR8 and miR-98-5p were conducted on OC cell lines SKOV-3 and A2780. Cell proliferation was detected with CCK8 and colony formation assay, and western blot was used to test the apoptotic levels of OC cells. Transwell assay was conducted to examine cell invasion and the epithelial-mesenchymal transition (EMT) of OC cells was tested by western blot. Moreover, luciferase activity assay and RNA immunoprecipitation (RIP) assay were conducted to verify the relationships between DSCR8 and miR-98-5p, miR-98-5p and STAT3. Results DSCR8 was remarkedly increased in OC tissues and associated with poorer survival of OC patients. Overexpressing DSCR8 promoted cell proliferation, invasion and EMT, but inhibited apoptosis. On the other hand, miR-98-5p was downregulated in OC tissues and relieved the progression of OC. Moreover, overexpressed DSCR8 increased the levels of STAT3 and HIF-1α and dampened the functions of miR-98-5p on OC. Pharmaceutical intervention of STAT3 and HIF-1α significantly altered the expressions of DSCR8 and miR-98-5p. Conclusion The present results suggested a positive feedback loop of lncRNA DSCR8/miR-98-5p/STAT3/HIF-α axis in the progression of OC.